Improvement of interprofessional communication competence through collaborative communication learning media - Sundari, Sri (Opción, 2019)
The paper provides the effect of interactive learning media that improves communication skill. It compares the differences of the student that has effective communication skill and not. Therefore, this study evaluates the effectiveness of interprofessional communication learning through the learning module and video. The differences in students collaborative communication skill of the two groups was measured using one-way ANOVA. As a result, the Control group showed significant differences in collaborative communication capability (p < 0,05). As a conclusion, interprofessional collaborative communication allows the student to process information in the material easily.